Utilization of Antenatal services and concerning factors: A community based study - Sharma, Arvind; Meshram, Priyanka K; Pandey, Dhruvendra; Kasar, Pradeep Kumar; Tiwari, Rajesh (Indian Journal of Community Health, 2018)
Background: Antenatal and post natal care are important component of maternal mortality rate. Antenatal facilities provided to mothers form the base of their future outcome. The services provided to mothers are still poor in India. A proper and effective program implementation is depending on understanding of basic factors that affect maternal and child health services utilization. Considering all these facts, it is important to study the maternal health service utilization pattern among the beneficiaries living in urban area of Jabalpur and factors responsible for their under utilization. Material & Methods: A prospective study was carried out in urban area of Jabalpur district of Madhya Pradesh. Cluster sampling technique was used to select 396 Antenatal females in the 36 different clusters. Information about socio demographic factors and ANC services utilization was recorded. Results: This study showed that 50.50% of women were registered within 12 weeks of pregnancy, 58.80% women received four or more antenatal visits, 23.99% women consumed hundred and more Iron Folic Acid (IFA) tablets and 96.21% received 2 doses of Tetanus Toxoid (TT) injections. Only 22.72% women had complete ANC service utilization. Conclusion: Utilization of Antenatal Care (ANC) services was poor in the urban areas of Jabalpur district even though the physical accessibility was adequate. ANC services utilization is significantly associated with level of education of mother, education of husband, occupation of mother, type of family and time of registration of pregnancy.